(untitled) (Global Journal of Medical Research, 2014)
Background: The hypertension in children need not be secondary. The essential hypertension is also increasing in trend. The available literature suggests that there is wide variation in the prevalence of hypertension. This study was taken up with the aim of studying the prevalence and factors responsible for hypertension in school children. Material and Methods: A cross sectional study was conducted to study the prevalence of hypertension in 1,734 school children in Chitradurga district from June 2011 to August 2011. A detailed history was taken in a predesigned proforma. The data thus obtained was compiled and analyzed. Results: The prevalence of hypertension in children in this study was 2.5% and more in females compared to males. The prevalence was higher after 10 years of age. Family history was one of the important risk factor for hypertension in children. The prevalence was also higher in children with higher BMI percentiles. Conclusion: Hypertension is not only common in children but also a neglected entity in children. This calls for urgent attention for the policy makers to begin the preventive measures as early as possible in the life to prevent the co morbidities.